A nomogram for predicting the probability of femoral head collapse in convalescent SARS patients with glucocorticoid-induced osteonecrosis of the femoral head: an 18-year population-based retrospective cohort study - Qu, Rundong; Gao, Fuqiang; Sun, Wei; Li, Zirong (Frontiers in Surgery, 2024)
Background: Based on an 18-year follow-up cohort of convalescent SARS patients with glucocorticoid-induced osteonecrosis of the femoral head (ONFH), this study aimed to develop a nomogram that can predict the probability of femoral head collapse.: Data of the natural history on 120 patients (205 hips) who underwent glucocorticoidinduced ONFH in China-Japan Friendship Hospital in 2003 were retrospectively collected. The follow-up was conducted from June, 2003 to October, 2021. A nomogram was developed in a training cohort and validated in another cohort.Results: 205 hips were included for analysis, 143 hips in the training cohorts and 62 hips in the validation cohorts. After 18 years of follow-up, 53 femoral heads collapsed and 152 femoral heads spontaneously repaired to some extent (necrotic areas reduced or vanished). Following multivariate regression analysis, the Association Research Circulation Osseous (ARCO) Staging, the index of necrosis (NI) and China-Japan Friendship Hospital (CJFH) Classification were entered into the nomogram. The nomogram showed a robust discrimination, with an AUC of 0.907 (95% CI: 0.85-0.96). The calibration curves showed an agreement between the probability as predicted by the nomogram and the actual probability. Application of the nomogram in the validation cohort still yielded good discrimination (AUC, 0.876, 95% CI: 0.7751-0.9761) and calibration.The nomogram achieved the prediction of femoral head collapse in glucocorticoidinduced ONFH. With the nomogram, the prognosis for an individual patient with glucocorticoidinduced ONFH can be determined, which can lead to a rational therapeutic choice.